Coupled Effects of Pore Water Velocity and Soil Heterogeneity on Bacterial Transport: Intact vs. Repacked Soils - Chen, Jing; Yang, Liqiong; Chen, Xijuan; Ripp, Steven; Zhuang, Jie (Frontiers in Microbiology, 2022)
Transport of pathogenic bacteria from land surface to groundwater is largely influenced by rainfall intensity and geochemical and structural heterogeneities of subsurface sediments at different depths. It has been assumed that the change in rainfall intensity has different effects on bacterial transport as a function of soil depth. In this study, repacked and intact column systems were used to investigate the influences of pore water velocity on the transport of Escherichia coli 652T7 through a loamy soil collected from varying soil depths. The soils differed in geochemical properties and soil structures. The concentrations of bacteria in soil and liquid samples were measured using plate counting method. The breakthrough percentages of E. coli 652T7 increased with pore water velocity at each depth in both intact and disturbed soils. Among the different soil depths, the largest velocity effect was observed for the transport through the top soil (0-5 cm) of both disturbed and intact soil profiles. This depth-dependent effect of pore water velocity was attributed to down gradients of soil organic matter (SOM) and iron oxide contents with depth because SOM and iron oxides were favorable for bacterial attachment on soil surfaces. In addition, less bacteria broke through the disturbed soil than through the intact soil at the same depth, and the pore water velocity effect was stronger with the disturbed than intact soils. Specifically, the maximum C/C0 (i.e., ratio of effluent to influent concentration) doubled (i.e., from 0.36 to 0.76) in the 0-5 cm intact soil columns and tripled (i.e., from 0.16 to 0.43) in the 0-5 cm repacked soil columns. This structure-dependent effect of pore water velocity was attributed to larger pore tortuosity and a narrower range of pore sizes in the disturbed soil than in the intact soil. These findings suggest that change in pore water velocity could trigger bacterial remobilization especially in surface soils, where more bacteria are retained relative to deep soils.